The Predicting Power of Family Support on Professional Maturity Level in Fine Arts: High School Students’ Choice of Profession - Yilmaz, Huseyin; Bastaban, Unal (Asian Journal of Contemporary Education, 2022)
In this study, the predictive power of family support on the level of professional maturity of students studying at Kars Fine Arts High School in the choice of profession was examined. The research was determined as a relational survey model, one of the survey models. The study group consisted of students studying at Kars Fine Arts High School in the 2019-2020 academic year. Data, the personal information form containing the demographic characteristics of the participants and the Professional Maturity Scale (PMS) and Family Support in Choosing a Profession scales were used to determine the level of professional maturity of family support in choosing a profession. In the analysis of the data, t-test, one-way ANOVA test, and regression analysis were performed for independent samples. It has been determined that the level of professional maturity of family support in choosing a profession differs according to the income level of the family. There is no significant difference in the department variable in the choice of profession. It has been seen that the power of family support to predict the level of professional maturity in the choice of profession of the students is the predictor of family support in the choice of profession.